Novel Focal Therapeutic Hypothermia Device for Treatment of Acute Neurologic Injury: Large Animal Safety and Efficacy Trial - Carlstrom, Lucas P.; Perry, Avital; Graffeo, Christopher S.; Dai, Daying; Ding, Yong H.; Jakaitis, Daniel R.; Lu, Aiming; Rodgers, Seth; Kreck, Thomas; Hoofer, Kelly; Gorny, Krzysztof R.; Kadirvel, Ramanathan; Kallmes, David F. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Therapeutic hypothermia is a potentially powerful and controversial clinical tool for neuroprotection following acute neurologic pathology, particularly vascular injury. Indeed, therapeutic hypothermia remains a standard of care for postcardiac arrest ischemia and acute neonatal hypoxic-ischemic encephalopathy, improving both survival and outcomes. Although therapeutic hypothermia remains promising for cellular and systems-based neuronal protection in other neurologic injury states, the systemic side effects have limited clinical utility, confounded analysis of potential neurologic benefits, and precluded the completion of meaningful clinical trials.Methods To address such limitations, we developed and tested a novel, minimally invasive, neurocritical care device that employs continuous circulation of cold saline through the pharyngeal region to deliver focal cerebrovascular cooling. We conducted a preclinical safety and efficacy trial in six adult porcine animals to assess the validity and functionality of the NeuroSave device, and assess cooling potential following middle cerebral artery occlusion (n = 2).Results NeuroSave consistently lowered brain parenchymal temperature by a median of 9°C relative to core temperature within 60 minutes of initiation, including in ischemic cerebral parenchyma. The core body temperature experienced a maximal reduction of 2°C, or 5% of body temperature, with no associated adverse effects identified.Conclusion The present study uses a large animal preclinical model to demonstrate the safety and efficacy of a novel, noninvasive device for the induction of robust and systemically safe hypothermia within the brain.
Keywords: therapeutic hypothermia; device; development; central nervous system cooling